Jump performance in junior divers: Relationship between field and laboratory measurements - Fornasiero, D.; Stanish, H.; Baker, J.; Daley, P.; Foley, S.; Logan, P.; Martin, D.
The data support the inclusion of five trials for maximal jump tests and indicate that in junior divers common laboratory jump tests performed using jump boards and timing mats can be used to reflect the ability to jump from a spring-board.